Effect of Some Spices Essential Oil and Extracts on Fermentation of Capers Buds - Argun, Muhammet; Musa Özcan*, Mehmet (Asian Journal of Chemistry, 2014)
The flower buds of caper plant were exposed to fermentation in 10 % brine for 6 weeks, with the addition of the volatile oils and extracts of different concentrations were obtained from the plants of sage, rosemary, dill, and coriander. Fermentation was monitored by chemical (acidity, salt, pH) and microbiological analyses. Depending on high salt concentrations, the bacteria of lactic acid did not develop. The values of acidity were found low. It was observed that the volatile oils and extracts were effective on microbial activity. The unique effects of distinctions in the sorts of spices did not clearly emerge. The value of salt concentration exhibited a rapidly decrease in the first week.